Globalization and international trade policies - Stern, Robert M. (World scientific studies in international economics, 2009)
Brings together a collection of papers that Robert M Stern and his co-authors have written. This collection addresses a variety of issues pertinent to the global trading system. It deals with globalization in terms of what the public needs to know about this phenomenon and the role of the World Trade Organization (WTO)